The vascular biology of macrophage migration inhibitory factor (MIF) - Asare, Yaw; Schmitt, Martin; Bernhagen, Jürgen (Thrombosis and Haemostasis, 2013)
Macrophage migration inhibitory factor (MIF) is a pleiotropic cytokine with chemokine-like functions. MIF is a critical mediator of the host immune and inflammatory response. Dysregulated MIF expression has been demonstrated to contribute to various acute and chronic inflammatory conditions as well as cancer development. More recently, MIF has been identified as an important pro-atherogenic factor. Its blockade could even aid plaque regression in advanced atherosclerosis. Promotion of atherogenic leukocyte recruitment processes has been recognised as a major underlying mechanism of MIF in vascular pathology. However, MIF’s role in vascular biology is not limited to immune cell recruitment as recent evidence also points to a role for this mediator in neo-angiogenesis / vasculogenesis by endothelial cell activation and endothelial progenitor cell recruitment. On the basis of introducing MIF’s chemokine-like functions, the current article focusses on MIF’s role in vascular biology and pathology.
Keywords: Chemokine; monocyte/macrophage; cardiovascular disease; atherosclerosis; (neo-)angiogenesis/vasculogenesis